The Effectiveness of Problem-Based Learning and Survey, Question, Read, Recite, Review to Improve Students’ Reading Comprehension - Yuliana, Yuliana; Rudi Hartono; Suwandi Suwandi (English Education Journal, 2024)
This study addresses the effectiveness of the PBL (Problem-Based Learning) method and the SQ3R (Survey, Question, Read, Recite, Review) method on students' reading comprehension, considering their different motivation levels, at SMPN 2 Gebog Kudus. The primary objective of this research is to compare the effectiveness of the PBL and SQ3R methods in enhancing reading comprehension among seventh-grade students with different motivation levels. This study employed an experimental research design, involving 30 seventh-grade students from SMPN 2 Gebog Kudus. The data were collected through questionnaires and tests. The questionnaire assessed students' perceptions of the PBL and SQ3R methods as well as their motivation in language learning. The tests measured students' reading comprehension before and after the intervention. SPSS Version 27 was used for data analysis, including hypothesis testing. The results indicated that the SQ3R method was more effective than the PBL method in improving reading comprehension among students with different motivation levels. The significance values for the tests are: (1) PBL method with high motivation: 0.012 (p < 0.05), PBL method with low motivation: 0.270 (p > 0.05), SQ3R method with high motivation: 0.017 (p < 0.05), SQ3R method with low motivation: 0.018 (p < 0.05). It can be concluded that the SQ3R method proved to be more effective than the PBL method in improving students' reading comprehension, especially when considering different motivation levels. This research contributes to enhancing critical thinking skills and learning outcomes in Junior High School (SMP) students, particularly in reading comprehension, through the application of the SQ3R method. It highlights the importance of incorporating effective methods such as SQ3R in teaching strategies to improve student performance in language learning.